SANDALI HEATERS FROM THE DERBENT EXCAVATIONS AND THEIR CENTRAL ASIAN AND POVOLJSKIY VARIANTS - Zilivinskaa, Emma Davidovna (History, Archeology and Ethnography of the Caucasus, 2020)
In 2014, large-scale secure-and-preserve digs were conducted in the coastal region of Derbent. Some interesting heating appliances were revealed during an excavation near the northern defense wall. They consisted of ceramic round pots buried in the floor of the premises, in which hot coals were placed. The aim of the study is to publish the information about these heaters and compare them with similar heating devices from other regions. A comparative analysis is made with archaeological sites of Central Asia and the Lower Volga region. Ethnographic data is also provided in the study. Hearths in the form of a pit with coals placed in it are widespread in Central Asia since ancient times, and are called “sandal” or “sandali”. A Central-Asian sandali commonly has the shape of a square pit laid with burnt bricks. This method of heating was used in residential premises and public spaces. Ethnographers recorded sandali heaters in various parts of Central Asia up to the second half of the 20th century. Pot-sandali is a local Caucasian variant of these heating appliances. In the Caucasus they were called “kursi”, though no ethnographic data about them have preserved to this day. The publication of materials of the Derbent excavations is aimed to fill this gap. Both “Central-Asian” and “Caucasian” variants of the sandal heaters have been found in the medieval monuments of the Lower Volga region, which indicates a significant influence of the North Caucasus on this region.